Kariery akademickie kobiet – uwikłania i inspiracje - Zaworska-Nikoniuk, Dorota (Rocznik Pedagogiczny, 2019)
In the article “Women’s Academic Careers – Entanglements and Inspirations”, I write about the significant problem of the specificity of female careers related to gender and its stereotypical percep- tion. The purpose of the research was to analyse the individual stages of women’s academic careers in the academic field of pedagogy (humanities and social sciences) in 2013–2019, based on the latest research reports (E. Kulczycki Report and the ‘Science in Poland’ Report). The study uses data about pedagogy as a feminized discipline, in which the majority of academic staff are female. The main research question was: How do the individual stages of women’s academic careers in social sciences (especially pedagogy) progress, and what factors determine them? The research method used in this study was what is often referred to in colloquial language as “desk research”, i.e. reviewing and analysing scientific literature, analysing data sources, compiling them and mutual verification. The interpretative background of this research was an analysis of the mechanisms of gender inequalities at universities (related to the mechanisms of the labour market).